2023
DOI: 10.3390/antibiotics12020279
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Related to Antibiotics Resistance in Helicobacter pylori Clinical Isolates from Bangladesh

Abstract: Current management of gastric inflammation involves the eradication of Helicobacter pylori. However, the effectiveness of commonly used antibiotics against H. pylori infection has decreased due to antibiotic resistance. Phenotypic-based diagnostics are laborious and finding the cause of resistance can be difficult. Therefore, early detection and understanding of the underlying mechanism of this resistance are necessary. This study evaluated the mutations in the genes related to the Antimicrobial Resistance (AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…18 In Hanoi (Northern Vietnam), the CLA resistance rate was extremely high at 96.7% in children with peptic ulcers, regardless of the pretreatment history. 37 However, our CLA resistance rate is approximately 2.5-3.5 times higher than reported for America (19%; 95% CI:13-26), Europe (24%; 95% CI: 19-30), and Southeast Asia (29%; 95% CI: [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], but similar to that in the Western Pacific region (85%; 95% CI: 80-90). 6 This may be related to CLA exposure during childhood, including the treatment of respiratory infections, self-medication with antibiotics, 31 over-the-counter purchase, and inadequate adherence to treatment regimens as CLA is an antibiotic in the first-line therapy for H. pylori.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…18 In Hanoi (Northern Vietnam), the CLA resistance rate was extremely high at 96.7% in children with peptic ulcers, regardless of the pretreatment history. 37 However, our CLA resistance rate is approximately 2.5-3.5 times higher than reported for America (19%; 95% CI:13-26), Europe (24%; 95% CI: 19-30), and Southeast Asia (29%; 95% CI: [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], but similar to that in the Western Pacific region (85%; 95% CI: 80-90). 6 This may be related to CLA exposure during childhood, including the treatment of respiratory infections, self-medication with antibiotics, 31 over-the-counter purchase, and inadequate adherence to treatment regimens as CLA is an antibiotic in the first-line therapy for H. pylori.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, several point mutations in the 23 s rRNA gene of H. pylori are associated with CLA resistance 38–40 . Through Sanger sequencing, we identified a high rate (98.4%) of a unique mutation at the A2143G nucleotide position.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…sively reported virulent and drug-resistant strains of H. pylori from Bangladesh, Ind China [21,22]. However, to the best of our knowledge, no comprehensive genom studies have been reported of H. pylori from Pakistan.…”
Section: Isolation Of H Pylorimentioning
confidence: 94%
“…H. pylori incidence is considerably high in South Asian populations. Such genome-based studies have compressively reported virulent and drug-resistant strains of H. pylori from Bangladesh, India, and China [21,22]. However, to the best of our knowledge, no comprehensive genome-based studies have been reported of H. pylori from Pakistan.…”
Section: Introductionmentioning
confidence: 99%